APLIKASI INFORMASI TEMPAT PARIWISATA DI KABUPATEN PASURUAN BERBASIS ANDROID MENGGUNAKAN METODE RAD (RAPID APPLICATION DEVELOPMENT) - Moerti, Hari; Haryanto, Kurniawan Wahyu; Andriyanto, Firman Eko (SPIRIT, 2025)
Abstract : As time goes by, traveling has become an important physical need without us realizing it. Pasuruan district has very broad tourism potential. The natural beauty, location and air conditions are very good, so it is visited by many local and foreign tourists. Not a few tourists have difficulty determining which tourist destination to visit because there is no application to get information, routes, restaurants and nearby hotels quickly, precisely and accurately in one place in order to increase interest in visiting Pasuruan Regency. To make the research easier the author uses the RAD (Rapid Application Development) method with four stages that need to be carried out, namely the first stage of needs planning, at this stage the writer will look for what information application users need, the second stage is system design at this stage the writer will design and improve the design application according to the needs of application users, the third stage of the development process and collecting feedback at this stage the researcher will change the system design in the form of a beta version of the application up to the final version. If the process goes smoothly then it can continue to the next stage, whereas if the application being developed has not answered the needs, the author will return to the system design stage, the fourth stage. Implementation or completion of the product. At this stage the author applies the application design of a system that was approved at the previous stage. . This research produces an Android application that provides information on tourist attractions in Pasuruan Regency and provides suggestions for hotels and restaurants closest to these tourist locations